The year of COVID-19: Personal reflections on how traditional pedagogy can be informed by online teaching methods (aka how I changed my mind about online teaching) - ONG, Ee-Ing (Institutional Knowledge at Singapore Management University, 2020)
Reflections on lessons learnt during online teaching during COVID-19. Despite the difficulties of the term, I realized that online teaching had certain strengths that traditional face-to-face teaching formats lacked. This started me on the path to adapting online teaching practices to improve our current modes of teaching, such as using online tools to improve interactivity, and reduce bias in interacting with students. I also started reconsidering whether our traditional classroom structures are indeed the best way to teach. While my experiences are based on teaching law, I believe that these points are also applicable to teaching in other disciplines.